Copper-Catalyzed Three-Component One-Pot Synthesis of Substituted 2-Aryl-1,3-benzoselenazoles - Su, Tao; Xie, Shishun; Li, Bifu; Yan, Jun; Huang, Ling; Li, Xingshu (Synlett, 2015)
A simple copper-catalyzed, one-pot synthesis of 2-aryl-1,3-benzoselenazole derivatives was developed using inexpensive, readily available 2-iodoanilines, selenium powder, and aromatic aldehydes as the starting materials. The mild reaction conditions and simple procedure without ligands and other additives make this methodology an alternative for preparing these potential selenium-containing compounds very conveniently.
Keywords: multicomponent reactions; heterocycle; 2-aryl-1,3-benzoselenazoles